Soccer injury in the lower extremities - Wong, P.; Hong, Y. (British Journal of Sports Medicine, 2005)
Information about soccer injuries is required to develop prevention and rehabilitation programmes. Most soccer injuries occur in the lower extremities. This type of injury is reviewed here. Definitions of injury, injury rate, injury percentage, mechanism of injury, anatomical region of injury, type of injury, and severity of injury are summarised. In each section, a description and summary of the data are provided. Finally, the limitations of the studies and suggestions to improve the investigation of soccer injuries are provided.